2022
DOI: 10.55951/nurture.v16i2.129
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Impulsive Buying Behavior: An Empirical Analysis of Consumers’ Purchase Intentions for Offline Beauty Products

Abstract: Purpose: The purpose of this research is to identify the underlying factors of impulsive buying behavior that would impact consumers’ buying behavior and eventually their purchase intentions.   Methodology: This research is based on the philosophy of positivism and employs a quantitative examination. In order to reach to our target market, we have used convenience sampling (non-probability sampling) and tried to gather the data in the original shopping environment i.e. a survey in shopping malls. A sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Impulsive buying behavior was observed in cluster two (C2), where consumers purchased items spontaneously due to fear of COVID-19 infection. It is in line with [11] that personal situations such as fear can trigger impulsive buying.…”
Section: Discussion Of the Results Of The Study On The Impact Of The ...supporting
confidence: 64%
See 1 more Smart Citation
“…Impulsive buying behavior was observed in cluster two (C2), where consumers purchased items spontaneously due to fear of COVID-19 infection. It is in line with [11] that personal situations such as fear can trigger impulsive buying.…”
Section: Discussion Of the Results Of The Study On The Impact Of The ...supporting
confidence: 64%
“…The study [11] identifies offline consumer buying behavior in the beauty industry. This study reported that consumers' moods, personal situations, store layout, product promotion, and product attributes positively impact impulsive buying.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Moreover, Trivedi et al (2023) contribute by exploring the effect of demographic factors on online impulse buying behavior, likely integrating demographic theories into impulsive buying research. A study by Tanveer et al (2022) on determinants of impulsive buying for offline beauty products offers a unique perspective, drawing on consumer intention and behavior theories specific to the beauty industry. These theoretical frameworks collectively provide a comprehensive understanding of the complex factors contributing to impulsive buying behavior.…”
Section: Literature Review and Hypotheses Development Impulsive Buyingmentioning
confidence: 99%
“…Promotional strategies, like flash sales and live-streaming shopping, serve as crucial situational factors impacting impulsive buying behavior, inducing spontaneous decisions (Huo et al, 2023;Lamis et al, 2022). Individual differences, particularly personality traits, contribute to understanding impulsive buying, as seen in Tanveer et al (2022) empirical analysis of consumers' purchase intentions for beauty products. Trivedi et al (2023) examine the effect of demographic factors and apparel product categories on online impulse buying, providing insights into how individual characteristics and product nature contribute to impulsive buying tendencies.…”
Section: Literature Review and Hypotheses Development Impulsive Buyingmentioning
confidence: 99%
“…The accessibility of funds in hand during purchases will enhance the purchasing desire of consumers. The rise in the availability of financial resources reduces the unpleasant feelings created by irritation with the inability to obtain affordable things (Tanveer, Kazmi & Rahman, 2022). Thus, it is hypothesised that: -H2:…”
Section: Situational Influence In Mobile Social Commerce and Its Effe...mentioning
confidence: 99%